Implementasi Nilai-Nilai Kearifan Lokal Budaya Pandeglang dalam Pembelajaran Kewarganegaraan di MI Darul Huda Pandeglang - Hidayat, Ahmad; Royhatudin, Aat (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2025)
This study aims to describe implementation of local wisdom values of Pandeglang culture in learning at MI Darul Huda Pandeglang. Local wisdom values such as mutual cooperation, respect for parents and teachers, tolerance, and love for the environment are an integral part of the culture of the Pandeglang community that have great potential to be instilled in the world of elementary education. The research approach used is qualitative with a case study method. Data collection techniques are carried out through observation, in-depth interviews with teachers and principals, and documentation of learning activities. The results of the study indicate that the application of local wisdom values has been carried out through integration in subjects such as Pancasila and Citizenship Education (PPKn), Indonesian Language, and local content. Teachers actively shape learning materials with a local cultural context through folklore, school community service activities, and the habituation of polite behavior. The obstacles faced include limited locally based teaching materials and the absence of curriculum guidelines that explicitly regulate the integration of local wisdom values. However, students' enthusiasm for materials associated with local culture shows that this approach is effective in building character and strengthening students' cultural identity. This study recommends the need for the development of a local culture-based curriculum and teacher training in integrating local wisdom values into the learning process